2012
DOI: 10.1016/j.ygyno.2012.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic oophorectomy rates in relation to a guideline update on referral to genetic counseling

Abstract: Objective We sought to determine whether prophylactic oophorectomy rates changed after the introduction of a 2007 health plan clinical guideline recommending systematic referral to a genetic counselor for women with a personal or family history suggestive of an inherited susceptibility to breast/ovarian cancer. Methods We conducted a retrospective cohort study of female members of Group Health, an integrated delivery system in Washington State. Subjects were women aged ≥35 years during 2004–2009 who reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Medicare typically only covers testing for individuals with a personal cancer history, meaning some clinically eligible women may have had out-of-pocket costs (16). Since 2007, the health plan's breast cancer screening guideline has recommended providers screen women aged 25 years and older for HBOC risk and refer those with personal and family histories suggestive of inherited susceptibility to the Department of Genetic Services or Medical Oncology for counseling and discussion of testing (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…Medicare typically only covers testing for individuals with a personal cancer history, meaning some clinically eligible women may have had out-of-pocket costs (16). Since 2007, the health plan's breast cancer screening guideline has recommended providers screen women aged 25 years and older for HBOC risk and refer those with personal and family histories suggestive of inherited susceptibility to the Department of Genetic Services or Medical Oncology for counseling and discussion of testing (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…1 Although we do not have data to directly assess this issue, we believe that our findings are robust; this is an average-risk cohort, and very few women are likely to have received these interventions. [2][3][4][5] This view is supported by 4 observations. First, Pocobelli et al 3 assessed a cohort of 18 390 women, including a subcohort from our analysis, who were 35 years or older and reported a personal or family history consistent with an inherited susceptibility to breast and/or ovarian cancer between 2004 and 2009.…”
Section: In Replymentioning
confidence: 63%
“…[2][3][4][5] This view is supported by 4 observations. First, Pocobelli et al 3 assessed a cohort of 18 390 women, including a subcohort from our analysis, who were 35 years or older and reported a personal or family history consistent with an inherited susceptibility to breast and/or ovarian cancer between 2004 and 2009. Those authors reported a low incidence rate for prophylactic oophorectomy of approximately 1 per 1000 person-years.…”
Section: In Replymentioning
confidence: 63%
See 1 more Smart Citation
“…1 Although we do not have data to directly assess this issue, we believe that our findings are robust; this is an average-risk cohort, and very few women are likely to have received these interventions. [2][3][4][5] This view is supported by 4 observations. First, Pocobelli et al 3 assessed a cohort of 18 390 women, including a subcohort from our analysis, who were 35 years or older and reported a personal or family history consistent with an inherited susceptibility to breast and/or ovarian cancer between 2004 and 2009.…”
Section: In Replymentioning
confidence: 63%